PENGAWASAN IZIN PRODUKSI DEPOT AIR MINUM ISI ULANG DAN AIR BERSIH KELILING DI KECAMATAN DUMAI TIMUR KOTA DUMAI - Musa "; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The production of refill drinking water and clean water depots still violates the rules, especially not having a business license, the eligibility of the equipment used and the feasibility of drinking water, this is due to a lack of supervision by the government. The Dumai City Health Office in carrying out the feasibility of producing refill drinking water and clean water depots in East Dumai District is inseparable from the determination of implementation standards, determination of measurement of activity implementation, measurement of activity implementation, comparison of implementation with standards and analysis of deviations and taking corrective action if necessary so that supervision activities can be carried out optimally. The purpose of this study was to determine the obstacles to the Supervision of Production Permits for Refill Drinking Water Depots and Mobile Clean Water in East Dumai District, Dumai City. The research method used is a qualitative method with data collection techniques through observation, interviews and documentation. The results of the study show that the Pekanbaru City Health Office in supervising the Production of Refill Drinking Water and Clean Water Depots has not been maximized, this is because routine supervision has not been carried out, imposition of sanctions so that there are still businesses that produce Refill Drinking Water and Clean Water Depots that do not have permits, standard eligibility use of equipment, and feasibility of drinking water. However, the authors suggest that the Dumai City Health Office should carry out routine surveillance, provide sanctions for businesses that do not have a permit, violate the provisions on the eligibility standards for the equipment used and the standards for drinking water. Keywords: Monitoring, Business, Clean Water